2002
DOI: 10.1097/00006534-200207000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy by Adenovirus-Mediated Vascular Endothelial Growth Factor and Angiopoietin-1 Promotes Perfusion of Muscle Flaps

Abstract: An experimental study was conducted to investigate the potential use of intravascular gene therapy with adenovirus-mediated (Ad) vascular endothelial growth factor (VEGF) or angiopoietin-1 (Ang-1) for the enhancement of muscle flap perfusion and to evaluate the effect of therapy on microcirculatory hemodynamics and microvascular permeability in vivo by using a cremaster muscle flap model in the rat. The cremaster tube flap was left intact after isolation of the pudo-epigastric pedicle. A total of 90 male Sprag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Ang1 overexpression in the heart resulted in smaller infarct zones and preserved cardiac function following myocardial infarctions. 29 -31 Improved myoblast survival and reduced tissue necrosis with hindlimb ischemia 96 and enhanced survival of muscle 59,60 and skin 97 flaps have also been reported. These studies showed increases in perfusion and/or capillary density, which were thought to explain the protective effects of Ang1 on the muscle and other tissues.…”
Section: Dallabrida Et Al Angiopoietin-1 Promotes Myocyte Survival E19mentioning
confidence: 98%
See 1 more Smart Citation
“…Ang1 overexpression in the heart resulted in smaller infarct zones and preserved cardiac function following myocardial infarctions. 29 -31 Improved myoblast survival and reduced tissue necrosis with hindlimb ischemia 96 and enhanced survival of muscle 59,60 and skin 97 flaps have also been reported. These studies showed increases in perfusion and/or capillary density, which were thought to explain the protective effects of Ang1 on the muscle and other tissues.…”
Section: Dallabrida Et Al Angiopoietin-1 Promotes Myocyte Survival E19mentioning
confidence: 98%
“…mediate skeletal muscle survival 59,60 during insults such as limb ischemia from peripheral vascular disease. We propose that this new angiopoietin function acts in concert with effects on the vasculature to protect the heart and peripheral tissues under adverse conditions.…”
Section: Dallabrida Et Al Angiopoietin-1 Promotes Myocyte Survival E15mentioning
confidence: 99%
“…5), confirming a property already described in literature. 6,13,14,22,39,40 Immunostaining the same samples with an antibody specific for a-Smooth Muscle Actin, emphasized the neoangiogenetic process taking place in AAV-VEGF-treated tissues, by demonstrating the massive presence of arterial vessels (Fig. 6), particularly in samples from group 9 (vector inoculation 14 days before surgery).…”
Section: Resultsmentioning
confidence: 95%
“…Studies have shown that adenovirus vector inserted with VEGF or liposome-mediated VEGF gene are effectively transferred and expressed via direct intramuscular injection or arterial access. [29,30] However, in addition to gene delivery techniques, the simplest method of gene delivery is the direct injection of naked plasmid DNA into tissues. Advantages of this method are local delivery to the target organ and the ability to act on non-dividing cells.…”
Section: Discussionmentioning
confidence: 99%